Ibn Arabi’s Thought on Waḥdat Al-Wujud and its Relevance to Religious Diversity - Umi Sumbulah (Ulumuna, 2016)
This article explains the concept of waḥdah al-wujūd and its relevance to the diversity of religions and beliefs. The idea of the unity of being developed by Ibn ʽArabī is an explanation about the existence of every entity which prevails in the universe. It means that nothing has essential substance except God. Therefore, all things that exist in the universe, including the diversity of religions and the pluralistic paths of faith, are rooted in God. The diversity of God’s laws occurs only due to the diversity of the doctrines revealed to the different prophets and apostles. So, Ibn ʽArabī, who has the typical philosophical thought of Sufism manifested through waḥdah al-wujūd, is considered as the supporter of the idea about the unity of religions emphasizing the inner aspect and the qualities of faith. This idea will tighten the relationship among those who love each other "within" God. DOI: http://dx.doi.org/10.20414/ujis.v20i1.793